MELATONIN VERSUS OMEGA-3 FATTY ACID AS POSSIBLE ANTIOXIDANTS AGAINST CYCLOPHOSPHAMIDE-INDUCED PULMONARY TOXICITY IN ADULT ALBINO RATS - RAGIA M. HEGAZY; EMAN M.FARUK; FAROUK S. ELGENDY; ESAM M. MEHLAB (International Journal of Pharma and Bio Sciences, 2015)
Cyclophosphamide (CP) is an anti-neoplastic and immunosuppressive agent used in organ transplantation and treatment of some autoimmune diseases. Melatonin (MT) has immunomodulatory antioxidant effects. Omega-3 is an essential fatty acid used as an antioxidant. The study aimed to compare the antioxidant role of MT versus omega-3 in the pulmonary toxicity of cyclophosphamide in rats. Sixty male rats were divided into four equal groups. Group Ι (Control group), Group ΙΙ: was given a single toxic dose of CP (200 mg/kg IP), Group ΙΙΙ: was given a melatonin intraperitoneal (10mg/kg/day for two weeks) concomitantly with CP and Group ΙV: was given fish oil through an intragastric tube (0.5 ml/kg/day for 2 weeks) concomitantly with CP. Histological, immuno- histochemical and biochemical studies had done to the rats’ lungs. CP significantly induced oxidative lung damage. In Group ΙΙΙ and ΙV there were significantly decreased lipid peroxidation and alterations in glutathione content (GSH), superoxide dismutase (SOD) and catalase induced by CP in lung tissues. Histological examination of the lungs in group II, revealed inflammatory cell infiltration with interstitial edema, hemorrhage, septal thickening, which markedly reduced in groups III and IV (P< 0.05), but this reduction was more marked with omega-3 (group IV). Also, groups III and IV, showed a significant decrease (P< 0.05) in cellular infiltration and extravasated RBCs, collagen fibers accumulation and in caspase-3 expression (P< 0.05) comparable to group II. Recommendation: concomitant administration of omega-3with CP is essential as it over melatonin against CP pulmonary toxicity.